VERB HYPONYMY CONTAINING THE MEANING OF 'TO TAKE' IN BETAWI MALAY LANGUAGE - Ririen Ekoyanantiasih (Metalingua: Jurnal Penelitian Bahasa, 2015)
IN Betawi Malay language there are many lexemes which have similar relationsof meaning. Some of which belong to synonymy while others belong to hyponymy.This article emphasizes the hyponymy of the verbs containing the meaning of "totake" using descriptive method. The data were taken from short stories and novelsin Betawi Malay Language and also the dictionary of Kamus Dialek Jakarta(1982). The data were analyzed using Nida's (1975) componential analysis oflexical meaning. The theory was based on the assumption that a lexeme consistsof a systematic semantics unit or contains a configuration of meaning whichcould be sorted into smallest components. The result showed that the lexeme bawewas the superordinate and its hyponymy was jungjung, dongdong, kandut, kempit,kepit, pikul, sandang, tengteng, jingjing, and keweng-keweng